2011
DOI: 10.1051/eas/1146010
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Spectroscopy of Protonated PAH Molecules Relevant For Interstellar Chemistry

Abstract: Abstract. In this contribution, we summarize the recent progress made in recording laboratory infrared (IR) spectra of protonated polycyclic aromatic hydrocarbon molecules (H + PAH) in the gas phase. The IR spectra of a large variety of H + PAH species ranging from benzene to coronene have been obtained by various variants of photodissociation spectroscopy. The employed techniques include single-photon IR photodissociation (IRPD) of tagged H + PAH ions and IR multiple-photon dissociation (IRMPD) of bare H + PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…From the astrochemical point of view, protonated polycyclic aromatic hydrocarbons (H + PAH) and their derivatives are predicted to be present in the interstellar medium (ISM) and are considered as possible carriers of the unidentified infrared emission (UIR) and diffuse interstellar bands (DIBs). ,, The high abundance of H 2 and H 3 + in the ISM converts PAH molecules into their protonated form via exothermic proton transfer, which in turn is unreactive toward both H and H 2 . , Microhydrated PAH and H + PAH clusters are also relevant in the context of understanding their presence, reactivity, and photochemistry inside ice grains or on their surfaces. It has been suggested that the PAH-ice interaction is responsible for the production of numerous organic molecules (e.g., alcohols, ketones, ethers) . Among the H + PAH cations, the prototypical H + Np ion and its hydrated clusters have received substantial interest with respect to both their interstellar abundance, chemical reactivity, and spectroscopy. ,, …”
Section: Introductionmentioning
confidence: 99%
“…From the astrochemical point of view, protonated polycyclic aromatic hydrocarbons (H + PAH) and their derivatives are predicted to be present in the interstellar medium (ISM) and are considered as possible carriers of the unidentified infrared emission (UIR) and diffuse interstellar bands (DIBs). ,, The high abundance of H 2 and H 3 + in the ISM converts PAH molecules into their protonated form via exothermic proton transfer, which in turn is unreactive toward both H and H 2 . , Microhydrated PAH and H + PAH clusters are also relevant in the context of understanding their presence, reactivity, and photochemistry inside ice grains or on their surfaces. It has been suggested that the PAH-ice interaction is responsible for the production of numerous organic molecules (e.g., alcohols, ketones, ethers) . Among the H + PAH cations, the prototypical H + Np ion and its hydrated clusters have received substantial interest with respect to both their interstellar abundance, chemical reactivity, and spectroscopy. ,, …”
Section: Introductionmentioning
confidence: 99%
“…31,[33][34][35] To this end, laboratory spectra of protonated aromatic molecules are highly requested. [36][37][38][39][40][41][42][43] In addition to the isolated aromatic ion, also the structure and spectroscopy of microhydrated clusters 16,18,19,22,26,44,45 are interesting in the context of their reactivity in ice grains and on ice surfaces. 22,[45][46][47][48] (2) Triggered by the astronomical detection of BN, we recently characterized BN + -L n clusters with nonpolar (L = Ar, n r 2), quadrupolar (L = N 2 , n r 4), and dipolar ligands (L = H 2 O, n = 1) by IRPD spectroscopy and DFT calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Protonated aromatic molecules have attracted much interest in the diverse fields of chemistry and biochemistry. Protonated aromatics are well-known crucial intermediates in electrophilic aromatic substitution reactions . The presence of protonated aromatics in interstellar space has been suggested. , Moreover, protonated aromatics are expected to play important roles in biochemical processes since the proton is one of the major carriers of positive charge in such systems .…”
Section: Introductionmentioning
confidence: 99%